Projeto de renovação de ar com split das salas de aula do andar superior do bloco de aulas 6 da UFERSA - Estrela, Allyson Ramon Lima (Universidade Federal Rural do Semi-Árido, 2019)
The renovation is done in collective environments that are cooled by splittype air conditioning, it is essential when you want to ensure the well being and health of everyone. Having this in hand was drafted in a way to do an air renovation project for classrooms one block from the university class that has this type of air conditioning. The work was done by calculating a thermal load and an air flow so that there is a renewal of air and from a system of considerable deficits, as well as a dispersion of pollutants and carbon dioxide. The results achieved were expected, considering that the practice of applying an update in Brazil is still not very old.
Monografia
Keywords: Ar-condicionado; Renovação; Bloco 6; Air-conditioning; Renovation; Block 6; ENGENHARIAS::ENGENHARIA MECANICA